Acquiring better insight into what it's like to have acquired brain injury - Durham, Christine (Henry Stewart Talks, 2011)
Brain injury shatters bodies, brains, spirits, lives, dreams and hope, Like being lost or shipwrecked, people with brain injury are like strangers in a strange land, With loss of memory and understanding, they're bewildered, humiliated, frustrated, in denial, unable to trust themselves, other people or the world around them. I know. I have brain injury, But people with brain injury can reflect, gain insight and understanding and then help themselves feel and fare better
Reviewed at 2020/10/12